Analisis Sentimen Penggunaan Artificial Intelligence Terhadap Penyelenggaraan Pemilu 2024 Menggunakan Metode LSTM-RNN - Juliansyah, Yaommi Juanpasha; Hilda, Atiqah Meutia (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The use of Artificial Intelligence (AI) in Indonesia's 2024 general election introduces new opportunities and challenges to the political process. AI is employed in various aspects, including political campaigns, voter data analysis, and election monitoring. While AI can enhance efficiency and accuracy, concerns about ethics, privacy, and its impact on transparency remain significant. This study aims to analyze public sentiment toward the use of AI in the 2024 election using a Long Short-Term Memory Recurrent Neural Network (LSTM-RNN) approach. Data were collected from various social media platforms, with a total of 768 data points analyzed. The LSTM-RNN model achieved an accuracy of 96%, demonstrating that this approach is effective in predicting and identifying public sentiment. The findings of this study are expected to provide valuable insights for political parties, campaign teams, and election organizers to better respond to public preferences. Additionally, this research is anticipated to contribute to the development of more effective campaign strategies while maintaining transparency and the integrity of the electoral process in the digital age.